(3eUGHjM GdTQjYI GdfHhjI GdeMeOjI GdefJRY GdeNJGQ ef Ydhe CFeI GdRjOjIs - (3Yaja GdOjf Ydj Hf SdjeGf GdOhGQj GdfLQGfjs
(3ChdgG (B:s
(3GdMeO ddg aGdb GdMH hGdfhi CeG HYO , aEfg NWQ Ydi bdHi Cf CLeY ai GdTQjYI GdfHhjI s
(3BNQgG (B:s
(3BNQg ef (B" (3HGH PcQ GdeQJOjf (B,(3GMcGege (B" (3bhdg (B: (3bGd GdTjN (B: (3hgh GdCbQH YfOfG GfJgi Je GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3fSNI CNQi efgs
(3ChdgG hBNQgG eced HNW eZGjQ s
(3hYdi MhGTjgG JYdjbGJ cKjQI s
(3cJHJ GdYfhGfGJ HNW eLhO hcJH HYVgG HGdMeQI s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs